Natural Xanthones and Skin Inflammatory Diseases: Multitargeting Mechanisms of Action and Potential Application - Gunter, Natalie Vivien; Teh, Soek Sin; Lim, Yang Mooi; Mah, Siau Hui (Frontiers in Pharmacology, 2020)
The pathogenesis of skin inflammatory diseases such as atopic dermatitis, acne, psoriasis, and skin cancers generally involve the generation of oxidative stress and chronic inflammation. Exposure of the skin to external aggressors such as ultraviolet (UV) radiation and xenobiotics induces the generation of reactive oxygen species (ROS) which subsequently activates immune responses and causes immunological aberrations. Hence, antioxidant and anti-inflammatory agents were considered to be potential compounds to treat skin inflammatory diseases. A prime example of such compounds is xanthone (xanthene-9-one), a class of natural compounds that possess a wide range of biological activities including antioxidant, anti-inflammatory, antimicrobial, cytotoxic, and chemotherapeutic effects. Many studies reported various mechanisms of action by xanthones for the treatment of skin inflammatory diseases. These mechanisms of action commonly involve the modulation of various pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor α (TNF-α), as well as anti-inflammatory cytokines such as IL-10. Other mechanisms of action include the regulation of NF-κB and MAPK signaling pathways, besides immune cell recruitment via modulation of chemokines, activation, and infiltration. Moreover, disease-specific activity contributed by xanthones, such as antibacterial action against Propionibacterium acnes and Staphylococcus epidermidis for acne treatment, and numerous cytotoxic mechanisms involving pro-apoptotic and anti-metastatic effects for skin cancer treatment have been extensively elucidated. Furthermore, xanthones have been reported to modulate pathways responsible for mediating oxidative stress and inflammation such as PPAR, Nrf2 and prostaglandin cascades. These pathways were also implicated in skin inflammatory diseases. Xanthones including the prenylated α-mangostin (2) and γ-mangostin (3), glucosylated mangiferin (4) and the caged xanthone gambogic acid (8) are potential lead compounds to be further developed into pharmaceutical agents for the treatment of skin inflammatory diseases. Future studies on the structure-activity relationships, molecular mechanisms, and applications of xanthones for the treatment of skin inflammatory diseases are thus highly recommended.